Temperature Influence on Non-Linear Harmonic Vibrations of Plates Made of Viscoelastic Materials - LITEWKA, Przemysław; LEWANDOWSKI, Roman (Engineering Transactions, 2020)
This paper is devoted to the analysis of ambient temperature influence on harmonic vibrations of von Kármán geometrically non-linear plates. The time-temperature superposition and the Williams-Landel-Ferry formula for the horizontal shift are used to modify the viscosity properties in the fractional Zener material model of viscoelasticity. The non-linear amplitude equation is obtained from the time-averaged principle of virtual work and the harmonic balance method. It is then solved after the finite element (FE) discretization using the continuation method to get the response curves in the frequency domain. Several numerical examples are solved and a significant influence of temperature on the resonance properties of the analysed plates is observed.